Sectoral trade freeness and agglomeration in the EU: An empirical test strategy - Gianluca Cafiso (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper studies the evolution of trade freeness and of the agglomeration of production, as well as their relationship, at the sectoral level in a group of EU countries. Our main objective is to test at the sectoral level the conclusions of previous aggregate analyses which find that an inverse relationship between trade costs and agglomeration holds in case of the Home Market Effect. Our sectoral focus requires an original testing approach based on the combination of different bootstrap distributions.
Keywords: F10; F12; F15; 330; trade freeness; agglomeration of production; home market effect; bootstrap